Sinomenine regulates immune cell subsets: Potential neuro-immune intervene for precise treatment of chronic pain - Lai, Wei-Dong; Wang, Song; You, Wen-Ting; Chen, Si-Jia; Wen, Jun-Jun; Yuan, Cun-Rui; Zheng, Meng-Jia; Jin, Yan; Yu, Jie; Wen, Cheng-Ping (Frontiers in Cell and Developmental Biology, 2022)
Abstract: Chronic pain is a disease of long-lasting pain with unpleasant feelings mediated by central and (or) peripheral sensitization, its duration usually lasts more than three months or longer than the expected recovery time. The patients with chronic pain are manifested with enhanced sensitivity to noxious and non-noxious stimuli. Due to an incomplete understanding of the mechanisms, patients are commonly insensitive to the treatment of first line analgesic medicine in clinic. Thus, the exploration of non-opioid-dependent analgesia are needed. Recent studies have shown that “sinomenine”, the main active ingredient in the natural plant “sinomenium acutum (Thunb.) Rehd. Et Wils.”, has a powerful inhibitory effect on chronic pain, but its underlying mechanism still needs to be further elucidated. A growing number of studies have shown that various immune cells such as T cells, B cells, macrophages, astrocytes and microglia, accompanied with the relative inflammatory factors and neuropeptides, are involved in the pathogenesis of chronic pain. Notably, the interaction of the immune system and sensory neurons is essential for the development of central and (or) peripheral sensitization, as well as the progression and maintenance of chronic pain. Based on the effects of sinomenine on immune cells and their subsets, this review mainly focused on describing the potential analgesic effects of sinomenine, with rationality of regulating the neuroimmune interaction. Keywords: sinomenine; sensory neurons; immune cells; glial cells; chronic pain